Environmental primer elaboration to aware children and young people - Uyeno, Marcio Takashi; Guizelini, Andressa De Angelis; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The human has explored the natural resources to survive and develop the place they live. In that context, the urban growth has contributed to the increase of environmental impacts, such as river pollution. In Maringá, a city in state of Paraná, there is the Morangueiro creek source, that is the main sub affluent of Pirapó river that is responsible for the water supply of Maringá and its surrounding region. Due the importance of this sub affluent, this study aims the write of an environmental education primer to conserve the valley bottom where Morangueiro creek source is located. To write the primer, visits where done to analyze and diagnose the study area through observation and photography registration. The result was a 30 pages environmental primer that will be used at schools children and young people awareness activities. The conclusion is that the primer elaboration is an important result to obtain the valley bottom conservation.